Stunting policy implementation in indonesia: A primary health care perspective - Suprapto Suprapto; Sri Wahyuni; Sarifudin Andi Latif (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Stunting remains a persistent public health challenge in Indonesia despite comprehensive national policies and multisectoral strategies. The primary issue lies not only in policy design but in its implementation at the primary health care level. This study aimed to examine how stunting policies are communicated, interpreted, and implemented, and to identify factors influencing implementation effectiveness within primary health care settings. Research Methodology: A qualitative, theory-informed design was employed using Edwards III’s policy implementation framework. Data were collected through semi-structured in-depth interviews with 25 purposively selected health workers, including nurses, midwives, nutritionists, and public health officers. Additional data sources included document reviews and observational notes. Thematic analysis was conducted to explore patterns related to communication, resources, implementer disposition, and bureaucratic structure. Results: Findings indicate that policy communication is predominantly top-down, with variable clarity and limited feedback mechanisms. Interpretation of policies is highly context-dependent, shaped by workload and local conditions. Implementation is largely integrated into routine maternal and child health services, with limited emphasis on preventive and multisectoral approaches. Key barriers include human resource constraints, insufficient funding, and rigid bureaucratic procedures. Despite these challenges, strong professional commitment among health workers emerged as a critical enabling factor supporting policy execution. Conclusion: The effectiveness of stunting policy implementation depends on strengthening communication clarity, resource allocation, and intersectoral coordination. Enhancing frontline engagement and reducing bureaucratic rigidity are essential to align policy intent with practice. A process-oriented approach to implementation improvement is necessary to achieve sustainable reductions in stunting.